Focused ultrasound versus the loop electrosurgical excision procedure to treat women with cervical high-grade squamous intraepithelial lesions under 40: a retrospective study - Linlin Xiao; Xu Dong; Jiangchuan Sun; Xuerui Zhang; Qing Feng; Shufang Chang (BMC Cancer, 2024)
Abstract Background This study aimed to compare the efficacy of focused ultrasound (FUS) and the loop electrosurgical excision procedure (LEEP) for the treatment of cervical high-grade squamous intraepithelial lesions (HSILs) among women of reproductive age. Methods Case records of patients aged < 40 years who were treated for cervical HSILs using either FUS or LEEP from September 1, 2020 to May 31, 2022 were retrospectively reviewed. Patients were followed up for cure, recurrence, human papillomavirus (HPV) clearance, and complications within 1 year of treatment. Odds ratios and 95% confidence intervals were determined using univariate and multivariate logistic regression models to analyze the association between disease evidence or HPV clearance and treatment modalities or other covariates. Results Of the 1,054 women who underwent FUS or LEEP, 225 met our selection criteria. Among the selected women, 101 and 124 received FUS and LEEP, respectively. There was no significant difference between the FUS and LEEP groups in the cure rate during the 3–6 months of follow-up (89.11% vs. 94.35%, P = 0.085) and recurrence rate during the 6–12 months follow-up (2.22% vs. 1.71%, P = 0.790). Both groups exhibited enhanced cumulative HPV clearance rates; however, the rates were not significantly different between the FUS and LEEP groups (74.23% vs. 82.79%, P = 0.122 during the 3–6 months follow-up; 84.95% vs. 89.17%, P = 0.359 during the 6–12 months follow-up). Furthermore, the incidence of complications caused by the FUS and LEEP techniques was comparable (5.0% vs. 5.6%, P = 0.818). Conclusions We found that FUS and LEEP have similar efficacy, safety, and reliability in treating women (aged < 40 years) with HSILs.